Evaluation of Brain Stem Function in Diabetics with and without Distal Symmetrical Polyneuropathy Using the Blink Reflex - Izzat, Sulaf E.; Saeed, Ghassan Th. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Diabetic peripheral neuropathy (DPN) is the most common complication of T2DM. Neuropathy is a descriptor for a spectrum of clinical and subclinical symptoms with varying anatomical distributions, clinical histories, and perhaps underlying pathogenetic mechanisms. The distal Symmetrical sensory polyneuropathy is chronic, symmetrical, length-dependent sensorimotor. Studies of the blink reflex have shown potential as a method of assessing brainstem activity.Objective: The primary purpose of this research was to assess the function of the blink reflex in the early detection of cranial nerves and brain stem dysfunction in diabetes patients with and without polyneuropathy. We also aimed to see whether there were differences in blink reflex abnormalities between individuals with and without polyneuropathy.Methods: The study included a group of sixty diabetic patients. Clinician and electrophysiologist evaluations were used to determine the severity of neuropathy. Patients with diabetes were separated into two groups: those with and without neuropathy.Results: A statistically significant difference between the two groups was found for C.R.2 latency and I.R.2 latency with a P-value